Scalable, Lithography-Free Plasmonic Metasurfaces by Nano-Patterned/Sculpted Thin Films for Biosensing - López-Muñoz, Gerardo A.; Cortés-Reséndiz, Armando; Ramón-Azcón, Javier; Rydosz, Artur (Frontiers in Sensors, 2022)
Scientific research in plasmonic metasurfaces has been widely widespread in the last years, motivated by the recent advances in the nanofabrication field and the increasing demand for high throughput sensing platforms. The recent advances in electronics, microfluidics, and signal processing have enabled the complete development of highly integrated devices with broad application potential. However, the progress observed from a fabrication point of view has been remarkable, led by the potential benefits metamaterials can offer in plasmonic sensing: sensor miniaturization, multiplexing opportunities, and extreme sensitivity biodetection. Although conventional top-down approaches, i.e., electron-beam lithography, have been extensively employed to develop plasmonic metasurfaces for biosensing, lithography-free bottom-up nanofabrication strategies based on nano-patterned/sculpted thin-films are candidates to surpass the limitations of top-down lithographic techniques with large-scale and high-throughput fabrication processes for 2D and 3D plasmonic metasurfaces over a broad material set. This perspective paper focuses on the challenges and opportunities to achieve lithography-free plasmonic metasurfaces by nano-patterned/sculpted thin films to conduct scalable and high-throughput plasmonic metamaterials for sensitive biosensing platforms.